Anabolic effects of IGF-1 signaling on the skeleton - Tahimic, Candice G. T.; Wang, Yongmei; Bikle, Daniel D. (Frontiers in Endocrinology, 2013)
This review focuses on the anabolic effects of IGF-1 signaling on the skeleton, emphasizing the requirement for IGF-1 signaling in normal bone formation and remodeling. We first discuss the genomic context, splicing variants and species conservation of the IGF-1 locus. The modulation of IGF-1 action by growth hormone (GH) is then reviewed while also discussing the current model which takes into account the GH-independent actions of IGF-1. Next, the skeletal phenotypes of IGF-1-deficient animals are described in both embryonic and postnatal stages of development, which include severe dwarfism and an undermineralized skeleton. We then highlight two mechanisms by which IGF-1 exerts its anabolic action on the skeleton. Firstly, the role of IGF-1 signaling in the modulation of anabolic effects of parathyroid hormone (PTH) on bone will be discussed, presenting in vitro and in vivo studies that establish this concept and the proposed underlying molecular mechanisms involving Indian hedgehog (Ihh) and the ephrins. Secondly, the crosstalk of IGF-1 signaling with mechanosensing pathways will be discussed, beginning with the observation that animals subjected to skeletal unloading by hindlimb elevation are unable to mitigate cessation of bone growth despite infusion with IGF-1 and the failure of IGF-1 to activate its receptor in bone marrow stromal cell cultures from unloaded bone. Disrupted crosstalk between IGF-1 signaling and the integrin mechanotransduction pathways is discussed as one of the potential mechanisms for this IGF-1 resistance. Next, emerging paradigms on bone-muscle crosstalk are examined, focusing on the potential role of IGF-1 signaling in modulating such interactions. Finally, we present a future outlook on IGF research.